Outcome and safety 90 days after combined airway valve treatment of the right upper and middle lobes in patients with severe pulmonary emphysema - A. Susanne Dittrich; Cosimo Carlo De Pace; Judith Maria Brock; Franziska Trudzinski; Claus Peter Heussel; Ralf Eberhardt; Felix J. F. Herth; Konstantina Kontogianni (Respiratory Research)
Abstract Background In COPD patients with severe right-sided emphysema, complete major and incomplete minor fissure, implantation of one-way valves in both the right upper (RUL) and middle lobes (ML) is a possible approach for endoscopic lung volume reduction. The aim of this retrospective analysis was to evaluate the response to therapy and the complication rate at 90 days (90d-FU) after combined RUL-ML valve implantation. Methods This retrospective, monocentric study included all patients from the Thoraxklinik Heidelberg who underwent RUL-ML valve treatment between 2012 and 2023 with available follow-up data. Quantitative chest imaging, lung function, 6-minute walking distance (6-MWD), complications and indications for re-bronchoscopies until 90d-FU were analysed. Results 28 patients underwent combined RUL-ML valve treatment, predominantly sequentially (92.86%, n = 26/28). Neither lung function nor 6MWD improved significantly in the overall cohort. However, in the subgroup with heterogeneous emphysema (71.4%, n = 20/28), FEV1 (Δ = 116.00 mL ± 195.77 mL, p < 0.05) and 6-MWD (Δ = 50.23 ± 69.10 m, p < 0.05) increased significantly at 90d-FU. Consistent with this, the baseline difference in emphysema volume between the RUL + ML and the right lower lobe correlated significantly with the increase in FEV1 at 90d-FU (R = 0.74, p < 0.001). Pneumothorax occurred in 5 cases in 4 patients (14.3%) following ML treatment. Severe pneumonia and/or COPD exacerbations occurred in 32.1% (9/28) of patients. Conclusions Although only studied in a small cohort, our data suggest that combined RUL and ML valve implantation appears to be a promising interventional treatment strategy in patients with severe heterogenous RUL and ML emphysema.